Instagram As A Media Of Communication Online Date - Susilo, Aldi Dwi; Octaviani , Vethy; Sari , Sapta (Social Sciences Journal, 2024)
In this modern era, there are many applications that can be used as a forum for online dating communication. Having applications like Instagram really helps people communicate long distances without having to be in the same location. From Instagram you can see the online dating process that occurs. Through the Instagram application, someone can do online dating which is relatively more effective in communicating online. In interacting using CMC, namely existence, time, form of communication and also use which allows someone to communicate without knowing time limits, the same existence and the communication that is formed is relatively more comfortable. This requires informants who have Instagram accounts that meet the criteria, such as the accounts @Luthfiyah, @fajar and @Riaayu. And the results showed that Instagram is very suitable as an online dating communication medium because the features available are relatively more complete and also safer in carrying out personal communication. On Instagram, someone can also post photos and videos that can be watched by other friends. According to the three informants, the online dating that occurred using Instagram ended in their relationship, or it could be said that they were officially dating.